Sculpture in Wood - Rood, John, 1902-1974 (Book collections on Project MUSE., 1950)
In simple every-day language and with lavish use of photographs, a noted sculptor takes you, step-by-step, through the process of wood sculpture and explains how to appreciate and use this kind of art in your own home. The how-to-do-it section contains information on the tools needed, the various woods and their qualities, and finishes. Photographs showing examples of the author's work and that of other contemporary sculptors illustrate his points clearly. The beginner will find this book opens the way to a rewarding hobby; the serious artist will be challenged by Mr. Rood's forceful ideas on.